Dysfunctional autophagy is a driver of muscle stem cell functional decline with aging. Issue 3 (3rd March 2016) - García-Prat, Laura; Muñoz-Cánoves, Pura; Martinez-Vicente, Marta
Abstract: Regeneration of skeletal muscle relies on its resident stem cells, also known as satellite cells, which are normally quiescent. With aging, satellite cell quiescence is lost concomitant with a muscle regenerative decline. Here we demonstrate that autophagy sustains quiescence over time and that its failure with age drives senescence, which accounts for stem cell loss of function. Pharmacological and genetic reestablishment of autophagy restores homeostasis and regenerative functions in geriatric satellite cells, which has relevance for the elderly population.